2016
DOI: 10.1002/ajp.22609
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of milk macronutrients and bioactive molecules across lactation in a western lowland gorilla (Gorilla gorilla) and a Sumatran orangutan (Pongo abelii)

Abstract: In addition to nutrients, milk contains signaling molecules that influence offspring development. Human milk is similar in nutrient composition to that of apes, but appears to differ in other aspects such as immune function. We examine the longitudinal patterns across lactation of macronutrients, the metabolic hormone adiponectin, the growth factors epidermal growth factor (EGF) and transforming growth factor β2 (TGF-β2), and two receptors for these growth factors (EGF-R and TGF-β2-RIII) in milk samples collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 59 publications
2
20
1
Order By: Relevance
“…This indicates that the bacterial community was gradually turning over with time. Nutrient content is largely stable in mature milk intra‐individually (Garcia et al, ; Hinde et al, ; Power et al, ), and we found no association of nutrient content predicting changes in the microbiome over time. Instead these changes over time may reflect EMT moving different bacteria from the mother's gut to the mammary gland and/or changes in the infant oral microbiome over time (Dzidic et al, ) that changes which bacteria colonize milk through retrograde flow during suction (Ascinar et al, ; Biagi et al, ).…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This indicates that the bacterial community was gradually turning over with time. Nutrient content is largely stable in mature milk intra‐individually (Garcia et al, ; Hinde et al, ; Power et al, ), and we found no association of nutrient content predicting changes in the microbiome over time. Instead these changes over time may reflect EMT moving different bacteria from the mother's gut to the mammary gland and/or changes in the infant oral microbiome over time (Dzidic et al, ) that changes which bacteria colonize milk through retrograde flow during suction (Ascinar et al, ; Biagi et al, ).…”
Section: Discussioncontrasting
confidence: 54%
“…Milk samples for nonhuman primates were collected either voluntarily or while under anesthesia. Samples were collected with approved protocols from NZP IACUC and Zoo Atlanta Scientific Review Committee for western lowland gorillas, Bornean orangutans ( Pongo pygmaeus ), and Sumatran orangutans (Garcia, Power, & Moyes, ; Power et al, ) and UCLA and UC Davis IACUCs for rhesus macaques ( Macaca mulatta ; Hinde, Power, & Oftedal, ). Bonobo ( Pan paniscus ), chimpanzee ( Pan troglodytes ), and owl monkey ( Aotus nancymaae ) samples were collected as part of standard management procedures in accordance with institutional guidelines for care and use of animals at their respective facilities (see Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the National Zoo gorilla in this study, many samples that were collected were from a complete evacuation of the mammary gland. There was no effect of whether the mammary expression was full or partial for any measured milk nutrient or the hormones adiponectin, epidermal growth factor, and transforming growth factor β‐2 (Power et al, ). The composition of a large milk sample (>30 ml) collected from the Pongo pygmaeus female under anesthesia from a prior birth (Milligan, ) was identical to the composition of the two small samples collected for this study.…”
Section: Discussionmentioning
confidence: 99%